2017
DOI: 10.1103/physrevd.95.043509
|View full text |Cite
|
Sign up to set email alerts
|

Big bounce, slow-roll inflation, and dark energy from conformal gravity

Abstract: We examine the cosmological sector of a gauge theory of gravity based on the SO(4,2) conformal group of Minkowski space. We allow for conventional matter coupled to the spacetime metric as well as matter coupled to the field that gauges special conformal transformations. An effective vacuum energy appears as an integration constant, and this allows us to recover the late time acceleration of the universe. Furthermore, gravitational fields sourced by ordinary cosmological matter (i.e. dust and radiation) are si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…After discussing briefly about the Hořava-Lifshitz gravity, we have formulated the modified field equations in logarithmic and Figs. [14][15][16] show the dynamical behaviors of the scale factor a, the sum of the energy density and pressure (ρ + p) and the energy density ρ during the bounce period for power law corrected model in fractal universe. power law versions of entropy corrected models in Hořava-Lifshitz gravity.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…After discussing briefly about the Hořava-Lifshitz gravity, we have formulated the modified field equations in logarithmic and Figs. [14][15][16] show the dynamical behaviors of the scale factor a, the sum of the energy density and pressure (ρ + p) and the energy density ρ during the bounce period for power law corrected model in fractal universe. power law versions of entropy corrected models in Hořava-Lifshitz gravity.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The evolution of the scale factor a, the sum of the energy density and pressure (ρ + p) and the energy density ρ during the bounce period for power law corrected model in fractal universe are shown in Figs. [14][15][16]. A barotropic equation of state p = γρ is assumed for the matter content.…”
Section: Case Ii: K = ±1mentioning
confidence: 99%
See 1 more Smart Citation
“…A bouncing universe has an initial narrow state by a minimal radius and then develops to an expanding phase [15], which means that the universe was arriving to the Big Bang era after the bouncing and so the equation of state parameter should cross from ω < −1 to ω > −1. Several studies in bouncing cosmology could be found in literatures [16][17][18][19][20][21][22]. On the other hand, the bouncing cosmology has also been studied in the framework of some modified theories of gravity eg.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers, (Edery & Paranjape 1998;Walker 1994;Yoon 2013), have shown that a linear potential of Mannheim type is incompatible with observations; in the present paper we show that a linear potential is not a consequence of the the field equations of conformal gravity, so these critiques are not needed. Gegenberg et al (2017) have used fourth-order gravity to try to understand inflation in the early Universe and accelerated expansion at late times (see also Gegenberg et al 2016;Gegenberg & Seahra 2018). This work deals with the Universe in the large, and is not directly connected with the present paper, which considers objects of the scale of galaxies or the Solar System.…”
Section: Introductionmentioning
confidence: 99%